Preservice Teachers Taking a Critical Stance When Examining Children's Literature. Issue 4 (1st October 2020) - Linder, Roberta; Falk-Ross, Francine
ABSTRACT: What does it mean to "read between the lines?" In today's society, print and nonprint texts may contain explicit or implicit messages promoting specific ideologies or biases, and future teachers need to be able to teach their students to read between the lines. Two teacher educators conducted a qualitative study in their literacy methods courses to determine if using a critical literacy graphic organizer would enable the preservice teachers to read more critically, uncover the sociopolitical issues underlying some children's literature, and realize the potential for classroom discussions around these issues. Results indicated that although the critical literacy graphic organizer guided the preservice teachers to gain new understandings about messages contained within children's literature, they experienced struggles with some aspects of a critical literacy approach.